Synonym, new species and checklist of the genus Fissocantharis Pic from Taiwan (Coleoptera, Cantharidae) - Yang, Yu-Xia; Okushima, Yûichi; Yang, Xing-Ke (Zootaxa, 2012)
Two new species of Fissocantharis Pic from Taiwan are described, F. flavipennis sp. nov. and F. laticornis sp. nov., andpresented with photos of habitus and illustrations of aedeagi, also each new species is provided with a key to the relatedspecies. Micropodabrus simplicicornis Wittmer, 1993 is synonymized with Fissocantharis formosana (Pic, 1910). A checklist of Fissocantharis from Taiwan is given.